Quantitative assessment of the degree of harmony between humanity and nature for national parks in China: A case study of the Three-River-Source National Park - Guo, Yanming; Liu, Xiaojie; Liu, Xiaohuang; Zhang, Jiahong; Zhang, Haiyan; Fan, Jiangwen; Khan, Nawab; Ma, Jiliang (Frontiers in Ecology and Evolution, 2023)
Introduction National parks, defined as the mainstay of the nature reserve system in China, pursue to achieve scientific protection and rational utilization of natural resources. However, eco-environmental and socioeconomic benefits are rarely considered together. Hereby, how to quantitatively express the relationship between humanity and nature in national parks needs further exploration. We selected the Three-River-Source National Park (TRSNP), China's largest national park by area and the world's highest altitude national park, as a representative case to construct an evaluation model for the degree of harmony between humanity and the nature of the national alpine ecological park. Methods Based on the field survey data, the meteorological data, the remote sensing data, and the socioeconomic data, the study used the model inversion and the spatial analysis methods to quantitatively evaluate the degree of harmony consisting of 12 indexes from a fresh perspective of a combination of the ecological environment and social economy. Considering the TRSNP establishment in 2016 as the time node, we assessed and compared the degree of harmony between humanity and nature during the dynamic baseline period (2011–2015) and the evaluation period (2016–2020). Results The results show that the degree of harmony between humanity and nature showed a gradual upward trend from the northwest to the southeast in the TRSNP. Compared with the dynamic baseline period, the eco-environmental and socioeconomic levels of the evaluation period were increased by 34.48 and 5.46%, respectively. Overall, the degree of harmony between humanity and nature visibly increased by 23.38%. Discussion This study has developed a novel comprehensive method for evaluating national parks at the regional scale for the win-win goal of both protection and development, and it provides a theoretical basis for effective planning and management policies for national parks.